Direct screening of a target-specific covalent binder: stringent regulation of warhead reactivity in a matchmaking environment. Issue 44 (12th May 2021) - Tabuchi, Yudai; Watanabe, Takahito; Katsuki, Riku; Ito, Yuji; Taki, Masumi
Abstract : To find targeted covalent biologics, we demonstrated a direct screening method of a peptidic covalent binder via reactivity/affinity-based co-selection using T7 phage display. Abstract : A peptide-type covalent binder for a target protein was obtained by direct and stringent screening of a warhead-modified peptide library on the robust T7 phage. The aryl fluorosulfate (fosylate) warhead was activated only in a matchmaking microenvironment created between the target protein and an appropriate peptide during the reactivity/affinity-based co-selection process of extended phage display.